The Impact of Stress on Odor Perception. (March 2017) - Hoenen, Matthias; Wolf, Oliver T.; Pause, Bettina M.
The olfactory system and emotional systems are highly intervened and share common neuronal structures. The current study investigates whether emotional (e.g., anger and fear) and physiological (saliva cortisol) stress responses are associated with odor identification ability and hedonic odor judgments (intensity, pleasantness, and unpleasantness). Nineteen men participated in the modified Trier Social Stress Test (TSST) and a control session (cycling on a stationary bike). The physiological arousal was similar in both sessions. In each session, participants' odor identification score was assessed using the University of Pennsylvania Smell Identification Test, and their transient mood was recorded on the dimensions of valence, arousal, anger, and anxiety. Multivariate regression analyses show that an increase of cortisol in the TSST session (as compared with the control session) is associated with better odor identification performance (β = .491) and higher odor intensity ratings (β = .562). However, increased anger in the TSST session (as compared with the control session) is associated with lower odor identification performance (β = −.482). The study shows divergent effects of the emotional and the physiological stress responses, indicating that an increase of cortisol is associated with better odor identification performance, whereas increased anger is associated with poorer odor identification performance.